Simplified Technique for Predicting Offshore Pipeline Expansion - Seo, J.H. (Harbin Engineering University, 2018)
In this study, we propose a method for estimating the amount of expansion that occurs in subsea pipelines, which could be applied in the design of robust structures that transport oil and gas from offshore wells. We begin with a literature review and general discussion of existing estimation methods and terminologies with respect to subsea pipelines. Due to the effects of high pressure and high temperature, the production of fluid from offshore wells is typically caused by physical deformation of subsea structures, e.g., expansion and contraction during the transportation process. In severe cases, vertical and lateral buckling occurs, which causes a significant negative impact on structural safety, and which is related to on-bottom stability, free-span, structural collapse, and many other factors. In addition, these factors may affect the production rate with respect to flow assurance, wax, and hydration, to name a few. In this study, we developed a simple and efficient method for generating a reliable pipe expansion design in the early stage, which can lead to savings in both cost and computation time. As such, in this paper, we propose an applicable diagram, which we call the standard dimensionless ratio (SDR) versus virtual anchor length (LA) diagram, that utilizes an efficient procedure for estimating subsea pipeline expansion based on applied reliable scenarios. With this user guideline, offshore pipeline structural designers can reliably determine the amount of subsea pipeline expansion and the obtained results will also be useful for the installation, design, and maintenance of the subsea pipeline. Â© 2018 Harbin Engineering University and Springer-Verlag GmbH Germany, part of Springer Nature